The mediation of trust in country-of-origin effects across countries. Issue 2 (29th April 2014) - Jiménez, Nadia; San Martín, Sonia
Abstract : Purpose: – This paper aims to investigate if trust plays a mediating role on the country-of-origin (COO) brand reputation and consumer animosity effects in determining consumers' purchase intentions in both emerging and developed markets. Design/methodology/approach: – The paper opted for the structure equation modelling methodology to analyse data collected from 476 Spanish and Mexican car owners who evaluate American automobiles. Findings: – The results show that in the emerging market economy, the COO's brand reputation influences trust and purchase intention more than in the mature market. Also, the results show that although trust plays an important role in different markets because it mediates the effect of COO's brand reputation on consumers' purchase intention in both emerging and mature economies, it does not mediate the effect of animosity on purchase intention in the analysed developed economy. Research limitations/implications: – The chosen category product presents the shortcoming of being of a hybrid nature regarding their manufacturing origin and research results may not be generalizable since we consider one product of one COO. Practical implications: – COO's brand reputation is a key trigger of trust, and can substitute absent regulatory institutional elements, especially in emerging markets. In emerging markets, animosity could play an important role in explaining the rejection of foreign products, but the increase of trust could mitigate its negative effect on purchase intention. Originality/value: – This study distinguishes the mediating role of trust between different interrelated COO variables and consumers' purchase intentions in two different national contexts, and offers evidence that good COO's brand reputation building is crucial for international marketing success.